Contraceptive Counseling for the Transgender Patient Assigned Female at Birth - Okano, Sérgio Henrique Pires; Pellicciotta, Giovanna Giulia Milan; Braga, Giordana Campos (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2022)
Although almost 0.7% of the Brazilian population identifies as transgender, there is currently no training for healthcare professionals to provide comprehensive care to these patients, including the discussion of reproductive planning. The use of testosterone promotes amenorrhea in the first months of use; however, this effect does not guarantee contraceptive efficacy, and, consequently, increases the risks of unplanned pregnancy. The present article is an integrative review with the objective of evaluating and organizing the approach of contraceptive counseling for the transgender population who were assigned female at birth. We used the PubMed and Embase databases for our search, as well as international guidelines on care for the transgender population. Of 88 articles, 7 were used to develop the contraceptive counseling model. The model follows the following steps: 1. Addressing the information related to the need for contraception; 2. Evaluation of contraindications to the use of contraceptive methods (hormonal and nonhormonal); and 3. Side effects and possible discomfort associated with the use of contraception. The contraceptive counseling model is composed of 18 questions that address the indications and contraindications to the use of these methods, and a flowchart to assist patients in choosing a method that suits their needs.
Keywords: transgender; contraception; testosterone